THE IMPLEMENTATION OF TEA PARTY STRATEGY IN TEACHING READING OF ANALYTICAL EXPOSITION TO THE ELEVENTH GRADERS (RETAIN, 2014)
Abstrak Membaca adalah salah satu skil yang wajib dikuasai oleh siswa. Akan tetapi, di dalam kelas membaca, teruatama membaca teks analytical exposition, siswa kurang motivasi dan merasa jenuh. Akibatnya, mereka kesulitan memahami teks yang mereka baca. Untuk mengatasi masalah tersebut, guru perlu menggunakan teknik mengajar yang dapat memotivasi siswa dalam membaca sekaligus mengaktifkan background knowledge mereka. Dalam hal ini, guru dapat menggunakan sebuah strategi pre-reading yang dikenal dengan Tea Party. Penelitian ini dirancang untuk mendeskripsikan penerapan strategi Tea Party dalam pengajaran membaca teks analytical exposition kepada siswa kelas sebelas. Pokok permasalahan dari penelitian ini antara lain: (1) Bagaimana penerapan strategi Tea Party dalam pengajaran membaca teks analytical exposition kepada siswa kelas sebelas? (2) Bagaimana respon siswa terhadap penerapan strategi Tea Party tersebut? Penelitian ini merupakan penelitian descriptive qualitative. Data-data disajikan secara deskriptif. Data pertama yakni tentang penerapan strategi Tea Party, diperoleh dari observasi sebanyak dua kali. Instrumen yang digunakan adalah unstructured field notes yang mendeskripsikan keseluruhan proses belajar mengajar. Data kedua, respon siswa terhadap penerapan strategi Tea Party, diperoleh dari hasil open-ended questionnaire. Hasil dari penelitian ini menunjukkan bahwa guru yang bersangkutan telah berhasil menerapkan strategi Tea Party. Motivasi siswa dalam membaca meningkat dan mereka dapat memahami teks analytical exposition yang mereka baca. Lebih lagi, hasil kuesioner menunjukkan bahwa siswa tertarik untuk membaca teks analytical exposition dan strategi Tea Party sangat membantu mereka dalam memahami teks tersebut. Maka, penerapan penerapan strategi Tea Party memberi banyak keuntungan yang positif bagi pengajaran membaca khususnya membaca teks analytical exposition. Kata Kunci: Membaca, teks analytical exposition, strategi Tea Party Abstract Reading is one of four main skills that students have to master. However, in reading class, especially reading of analytical exposition, the students lack of motivation and get bored. As a result, they feel difficult to comprehend the text they read. To solve this problem, teacher needs to use a reading strategy which can motivate the students to read as well as activate their background knowledge. Due to the need, the teacher can use a pre-reading strategy named Tea Party. This research is designed to describe the implementation of Tea Party strategy in teaching reading of analytical exposition to the eleventh graders. The points of this research are on (1) How is the implementation of Tea Party strategy in teaching reading of analytical exposition to the eleventh graders of SMAN 1 Karangbinangun? (2) How are the students’ responses toward the implementation of Tea Party strategy? This research is descriptive qualitative research. The data were served in descriptive details. The first data which was about the implementation of Tea Party strategy obtained through two-time observations. The instrument used was unstructured field notes which describe the whole teaching and learning process done by the teacher in the class. The second data, the students’ responses toward the implementation of Tea Party strategy, was obtained using open-ended questionnaire. This research showed that the teacher implemented Tea Party strategy successfully. The students’ motivation on reading increased and they could comprehend the analytical exposition text they had read. Furthermore, the result of questionnaire showed that the students felt interested in reading the text. It also showed that Tea Party was helpful to students in comprehending the text. Therefore, the implementation of Tea Party strategy gives positive benefits to teaching reading especially reading of analytical exposition. Keywords: Reading, analytical exposition, Tea Party strategy